Method for regulating and controlling degradation rate of biological magnesium alloy in urinary system
By smelting, homogenizing heat treatment and friction stir processing of the magnesium alloy, a biomagnesium alloy suitable for the urinary system was prepared, which solved the problem of excessively fast degradation rate of magnesium alloy, and achieved the regulation of degradation rate and the improvement of biocompatibility.
Patent Information
- Application Number
- CN202411923649.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The degradation rate of magnesium alloys in the urinary system is too fast and uneven, limiting its development in the biological field, especially in different application environments and patient ages, and it is difficult to meet the demand for degradation rate.
By melting the magnesium alloy raw material under a protective atmosphere, then homogenizing heat treatment under an inert atmosphere, and finely adjusting the matrix material by using friction stir processing technology, a biomagnesium alloy suitable for the urinary system was prepared.
The degradation rate of biomagnesium alloy is regulated, which meets the degradation rate of different needs in the urinary system, and ensures the biocompatibility and safety of the material.
Smart Images

Figure CN119710506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical materials, and in particular to a method for regulating the degradation rate of biological magnesium alloys in a urinary system. Background Art
[0002] Magnesium alloys have the advantages of low density, high specific strength, specific stiffness and good biocompatibility, and have broad application prospects in traditional industries and biomedicine. In recent years, magnesium alloys have shown great application potential as degradable biomaterials in orthopedics, cardiovascular and urinary systems. However, due to the strong activity and poor corrosion resistance of magnesium alloys, their degradation rate is too fast and the degradation process is uneven during the application process, which greatly limits the development of magnesium alloys in the biological field. In different application environments, the ideal degradation time of implant materials is also very different. For example, the degradation rate of magnesium alloys in the urinary system is relatively shorter than that of orthopedics and cardiovascular systems (degradation is completed within 2 to 4 weeks), and patients of different age groups have different requirements for the degradation rate of implant materials. Therefore, the controllability of the degradation rate of biological magnesium alloys in the urinary system is of great significance for its subsequent application. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The purpose of the present invention is to provide a method for regulating the degradation rate of biological magnesium alloy in the urinary system.
[0004] Specifically, the present invention provides the following technical solutions:
[0005] In a first aspect of the present invention, a method for regulating the degradation rate of biological magnesium alloy in the urinary system is provided, comprising:
[0006] S1: smelting the magnesium alloy raw material in a protective atmosphere to obtain a magnesium alloy ingot;
[0007] The magnesium alloy raw material is composed of the following components in weight percentage: Y (yttrium): 2-3wt.%, Nd (neodymium): 1-2wt.%, Gd: 0-1wt.%, Zn: 0-1wt.%, Ca: 0-1wt.%, Sr (strontium): 0-1wt.%, and the balance is magnesium and other impurity elements;
[0008] S2: performing homogenization heat treatment on the magnesium alloy ingot under an inert atmosphere, and cooling the ingot to obtain a matrix material;
[0009] S3: performing friction stir processing on the base material to obtain a bio-magnesium alloy of a predetermined size.
[0010] The method provided by the present invention can realize the regulation of the degradation rate of biological magnesium alloy.
[0011] According to an embodiment of the present invention, the method for regulating the degradation rate of biological magnesium alloy in the urinary system provided above may further include the following technical features:
[0012] In some embodiments of the present invention, the protective atmosphere in step S1 is a mixed gas of CO2 and SF6;
[0013] In some embodiments of the present invention, the ratio of the volume fractions of CO2 and SF6 is (95-99):(1-5). According to a preferred embodiment, the protective atmosphere in step S1 is a mixed gas of CO2 and SF6, and the volume fraction ratio is 99:1.
[0014] In some embodiments of the present invention, the magnesium alloy raw material includes raw materials of the following compositions: intermediate alloy Mg-30wt.%Y, intermediate alloy Mg-30wt.%Nd, intermediate alloy Mg-30wt.%Gd, intermediate alloy Mg-20wt.%Sr, pure Mg, pure Zn and pure Ca raw materials.
[0015] In some embodiments of the present invention, the temperature of the smelting treatment is 650-750° C., and the time of the smelting treatment is 10-30 minutes.
[0016] In some embodiments of the present invention, in step S2, a heat treatment for component homogenization is performed under the protection of an argon atmosphere. According to a specific embodiment, the heat treatment temperature is 300° C.-450° C., and the time is 12-24 hours.
[0017] In some embodiments of the present invention, in step S3, the stirring head used in the friction stir processing is a tungsten-rhenium alloy.
[0018] In some embodiments of the present invention, in step S3, the forward speed of the stirring head used in the friction stir processing is 10-200 mm / min.
[0019] In some embodiments of the present invention, in step S3, the stirring head used in the friction stir processing has a rotation speed of 100-1500 r / min.
[0020] In some embodiments of the present invention, in an artificial urine environment, the corrosion current density of the biological magnesium alloy is 10-500 μA / cm 2 The degradation rate is 0.5~40mm / y.
[0021] In a second aspect of the present invention, a method for preparing a biological magnesium alloy for a urinary system is provided, comprising:
[0022] S1: melting the magnesium alloy raw material under a protective atmosphere to obtain a magnesium alloy ingot;
[0023] Wherein, the magnesium alloy raw material includes Y: 2-3wt.%, Nd: 1-2wt.%, Gd: 0-1wt.%, Zn: 0-1wt.%, Ca: 0-1wt.%, Sr: 0-1wt.%, and the balance of magnesium and other impurity elements;
[0024] S2: performing homogenization heat treatment on the magnesium alloy ingot under an inert atmosphere, and cooling the ingot to obtain a matrix material;
[0025] S3: performing friction stir processing on the base material to obtain a bio-magnesium alloy of a predetermined size.
[0026] In a third aspect of the present invention, a bio-magnesium alloy is provided, which is prepared according to the method described in any one of the first aspect or the second aspect.
[0027] The fourth aspect of the present invention provides use of the bio-magnesium alloy described in the third aspect in preparing biomaterials for the urinary system.
[0028] The technical solution of the present invention includes at least the following beneficial effects:
[0029] The present invention provides a preparation and processing method for adjusting the degradation rate of magnesium alloy in the urinary system by synergistically adjusting the key process parameters of the components, ratios and processing methods, introducing alloy elements with good biocompatibility through rational design, and finely regulating the microstructure of the prepared magnesium alloy using stir friction processing technology. The specific advantages are as follows:
[0030] The element composition and content added to the magnesium alloy raw material used in the present invention are comparable to and fully meet the international requirements for biomedical implant materials, have good biosafety and biocompatibility, the alloy element content is controlled below 8wt.%, and the rare earth element addition amount is controlled below 6wt.%.
[0031] The preparation method provided by the present invention includes a stir friction processing technology, which can achieve fine control of the microstructure of the magnesium alloy after casting, and achieve control of the degradation rate of the biological magnesium alloy by adjusting and modifying the grain size, the solid solubility of elements in the matrix, the size and distribution of the precipitated phase in the prepared magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Surface SEM morphology of the magnesium alloy matrix material prepared in Example 1 of the present invention and the bio-magnesium alloy sample after friction stir processing (FSP).
[0033] Figure 2These are the polarization curve test results of the magnesium alloy matrix material prepared in Example 2 of the present invention and the biological magnesium alloy sample after stir friction processing in artificial urine.
[0034] Figure 3 The results of hydrogen evolution test during the degradation process of the magnesium alloy matrix material prepared in Example 4 of the present invention and the biological magnesium alloy sample after stir friction processing in artificial urine.
[0035] Figure 4 Surface SEM morphology of the magnesium alloy matrix material prepared in Example 5 of the present invention and the biological magnesium alloy sample after stir friction processing after long-term degradation in artificial urine.
[0036] Figure 5 The figure is a bar graph showing the degradation rates of the bio-magnesium alloy samples prepared according to different embodiments of the present invention in artificial urine. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0038] The present invention proposes a preparation and processing method for regulating the degradation rate of biological magnesium alloy in the urinary system, the method comprising:
[0039] [Step S1] Melting of magnesium alloy
[0040] This step is to obtain a magnesium alloy ingot by smelting the magnesium alloy raw material under a protective atmosphere. In this step, the magnesium alloy raw material is supplied to a resistance furnace for smelting, wherein the magnesium alloy raw material is configured according to the following mass percentage ratio: Y: 2-3wt.%, Nd: 1-2wt.%, Gd: 0-1wt.%, Zn: 0-1wt.%, Ca: 0-1wt.%, Sr: 0-1wt.%, and the balance is magnesium and impurity elements. The inventors found that the introduction of a small amount of rare earth elements can effectively improve the mechanical strength of magnesium alloys without being toxic to organisms, and zinc and calcium elements are essential elements for the human body. Through rational design, the magnesium alloy system achieves ideal degradation behavior and has good biocompatibility. According to a specific embodiment, the content of Zn is not 0, preferably 0.3-0.8wt%. According to a specific embodiment, the content of Ca is not 0, preferably 0.3-0.8wt%. According to a specific embodiment, the content of Gd is not 0, preferably 0.5-1wt%. According to a specific embodiment, the Sr content is not 0, and is preferably 0.5 to 1 wt%.
[0041] The "impurity elements" mentioned refer to other chemical elements that are inevitably present in bio-magnesium alloys. Including but not limited to iron (Fe), nickel (Ni), aluminum (Al), manganese (Mn), copper (Cu), etc., the presence of impurity elements usually affects the corrosion ability and mechanical properties of bio-magnesium alloys. The content of impurity elements should be controlled at a very small level, for example, the total amount of impurity elements should be controlled to be less than 0.1%. According to a specific embodiment, the content of impurity elements in bio-magnesium alloys must comply with the standards and specifications in this field. For example, the impurity element content of medical bio-magnesium alloys usually needs to comply with specific standards and specifications, such as iron should not exceed 45ppm, nickel should not exceed 280ppm, etc. In addition, for impurity elements for which the limit values are not clearly specified, if their content is greater than 0.010%, they should be included in the total impurities, etc.
[0042] Specifically, Y, Nd, Gd, and Sr can be added in the form of an intermediate alloy, and Zn and Ca can be added in the form of a single substance. According to a specific embodiment, the intermediate alloy Mg-30wt.%Y, Mg-30wt.%Nd, Mg-30wt.%Gd, Mg-20wt.%Sr, pure Mg, pure Zn, and pure Ca raw materials are proportioned and placed in an alumina crucible, and placed in a resistance furnace, and heated to 650-750°C under a protective atmosphere, and the insulation time is 10-30min to obtain a magnesium alloy ingot sample. Herein, pure in pure Mg, pure Z, and pure Ca refers to a content of more than 99.9%; according to a preferred embodiment, the content of pure Mg is more than 99.99%, the content of pure Zn is more than 99.9%, and the content of pure Ca is more than 99.9%.
[0043] According to a specific implementation method, the temperature rise range of the resistance furnace is 650-750° C., and the insulation time is 10-30 minutes.
[0044] According to a specific implementation, the protective atmosphere in step S1 is a mixed gas of CO2 and SF6, and the volume fraction ratio is 99:1.
[0045] [Step S2] Homogenization
[0046] In this step, the magnesium alloy ingot obtained in S1 is subjected to homogenization heat treatment in an argon protective atmosphere to improve the microstructure and properties of the casting alloy.
[0047] According to a specific implementation, the heat treatment temperature in step S2 is 300°C-450°C, and the time is 12-24h.
[0048] After the homogenization heat treatment, the matrix material is obtained by cooling to room temperature.
[0049] [Step S3] Friction stir processing
[0050] The obtained matrix material is subjected to stir friction processing to refine its microstructure. The degradation rate of the bio-magnesium alloy is regulated by modifying the grain size, the solid solubility of elements in the matrix, the size and distribution of the precipitated phase in the prepared magnesium alloy.
[0051] In this step, the surface of the magnesium-rare earth alloy is polished to remove the oxide scale on the surface, and then the magnesium alloy is processed. The stirring head material of the processing process is tungsten-rhenium alloy, and the dimensions of the stirring head are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm.
[0052] In some embodiments, the stirring head used in the friction stir processing in step S3 has a rotation speed of 100-1500 r / min and a forward speed of 10-200 mm / min.
[0053] According to the embodiment of the present invention, through the design of the bio-magnesium alloy components and the subsequent processing process, the degradation rate can be adjusted over a wide range. As a result, the corrosion current density of the prepared alloy in an artificial urine environment is 10 to 500 μA / cm 2 , the degradation rate is 0.5~40mm / y), which can meet the different needs of ureteral stent implant materials in the urinary system and achieve reasonable controllability.
[0054] The technical scheme of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. Unless otherwise specified, the reagents or raw materials used in the examples can be obtained commercially.
[0055] Example 1
[0056] Example 1 provides a method for regulating the degradation rate of biological magnesium alloy in the urinary system, which specifically includes the following steps:
[0057] S1, smelting of magnesium alloy: supply magnesium alloy raw materials to a resistance furnace for smelting, wherein the above magnesium alloy raw materials are configured according to the following mass percentage ratio: Y: 3wt.%, Nd: 1wt.%, Gd: 1wt.%, Zn: 0.5wt.%, Ca: 0.5wt.%, and the balance is Mg and other impurity elements. Put the raw materials into a ceramic crucible, and under the protection of a mixed gas atmosphere of 99% CO2-1% SF6, raise the temperature of the resistance furnace to 680°C, keep it warm for 30 minutes, and take out the magnesium alloy ingot after the furnace cools down.
[0058] S2, homogenization treatment: subjecting the magnesium alloy ingot to a component homogenization heat treatment under the protection of an argon atmosphere, wherein the heat treatment temperature is 450° C. and the time is 12 h. The treated ingot is cooled to room temperature in the furnace to obtain a matrix material.
[0059] S3, processing process: first, the homogenized matrix material is cut into plates with a size of 200mm×65mm×4mm by wire cutting, and then the magnesium-rare earth alloy plate is surface polished to remove the oxide scale on the surface of the magnesium alloy, and then the magnesium alloy plate is subjected to stir friction processing. The stirring head is made of tungsten-rhenium alloy, and the stirring head dimensions are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm. The stirring head speed is 100rpm, and the forward speed is 50mm / min, and then the magnesium alloy sample after stir friction processing is obtained.
[0060] Example 2
[0061] Example 2 provides a method for regulating the degradation rate of biological magnesium alloy in the urinary system, which specifically includes the following steps:
[0062] S1, smelting of magnesium alloy: supply magnesium alloy raw materials to a resistance furnace for smelting, wherein the above magnesium alloy raw materials are configured according to the following mass percentage ratio: Y: 3wt.%, Nd: 1wt.%, Gd: 1wt.%, Sr: 1wt.%, and the balance is Mg and other impurity elements. Put the raw materials into a ceramic crucible, and under the protection of a mixed gas atmosphere of 99% CO2-1% SF6, raise the temperature of the resistance furnace to 660°C, keep it warm for 30 minutes, and take out the magnesium alloy ingot after the furnace cools down.
[0063] S2, homogenization treatment: subjecting the magnesium alloy ingot to a component homogenization heat treatment under the protection of an argon atmosphere, wherein the heat treatment temperature is 400° C. and the time is 12 h. The treated ingot is cooled to room temperature with the furnace to obtain a matrix material.
[0064] S3, processing process: first, the homogenized matrix material is cut into plates with a size of 200mm×65mm×4mm by wire cutting, and then the magnesium-rare earth alloy plate is surface polished to remove the oxide scale on the surface of the magnesium alloy, and then the magnesium alloy plate is subjected to stir friction processing. The stirring head is made of tungsten-rhenium alloy, and the stirring head dimensions are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm. The stirring head speed is 500rpm, and the forward speed is 50mm / min, and then the magnesium alloy sample after stir friction processing is obtained.
[0065] Example 3
[0066] Example 3 provides a method for regulating the degradation rate of biological magnesium alloy in the urinary system, which specifically includes the following steps:
[0067] S1, smelting of magnesium alloy: supply magnesium alloy raw materials to a resistance furnace for smelting, wherein the above magnesium alloy raw materials are configured according to the following mass percentage ratio: Y: 3wt.%, Nd: 1wt.%, Gd: 1wt.%, Zn: 1wt.%, Ca: 1wt.%, Sr: 0.5wt.%, and the balance is Mg and other impurity elements. Put the raw materials into a ceramic crucible, and under the protection of a mixed gas atmosphere of 99% CO2-1% SF6, raise the temperature of the resistance furnace to 750°C, keep it warm for 10 minutes, and take out the magnesium alloy ingot after the furnace cools down.
[0068] S2, homogenization treatment: subjecting the magnesium alloy ingot to a component homogenization heat treatment under the protection of an argon atmosphere, wherein the heat treatment temperature is 420° C. and the time is 24 hours. The treated ingot is cooled to room temperature in the furnace to obtain a matrix material.
[0069] S3, processing process: first, the homogenized matrix material is cut into plates with a size of 200mm×65mm×4mm by wire cutting, and then the magnesium-rare earth alloy plate is surface polished to remove the oxide scale on the surface of the magnesium alloy, and then the magnesium alloy plate is subjected to stir friction processing. The stirring head is made of tungsten-rhenium alloy, and the stirring head dimensions are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm. The stirring head speed is 300rpm, and the forward speed is 100mm / min, and then the magnesium alloy sample after stir friction processing is obtained.
[0070] Example 4
[0071] Example 4 provides a method for regulating the degradation rate of biological magnesium alloy in the urinary system, which specifically includes the following steps:
[0072] S1, smelting of magnesium alloy: supply magnesium alloy raw materials to a resistance furnace for smelting, wherein the above magnesium alloy raw materials are configured according to the following mass percentage ratio: Y: 3wt.%, Nd: 1wt.%, Gd: 1wt.%, Ca: 1wt.%, and the balance is Mg and other impurity elements. Put the raw materials into a ceramic crucible, and under the protection of a mixed gas atmosphere of 99% CO2-1% SF6, raise the temperature of the resistance furnace to 720°C, keep it warm for 30 minutes, and take out the magnesium alloy ingot after the furnace cools down.
[0073] S2, homogenization treatment: subjecting the magnesium alloy to a component homogenization heat treatment under the protection of an argon atmosphere, wherein the heat treatment temperature is 450° C. and the time is 12 h. The treated ingot is cooled to room temperature with the furnace to obtain a matrix material.
[0074] S3, processing process: first, the homogenized matrix material is cut into plates with a size of 200mm×65mm×4mm by wire cutting, and then the magnesium-rare earth alloy plate is surface polished to remove the oxide scale on the surface of the magnesium alloy, and then the magnesium alloy plate is subjected to stir friction processing. The stirring head is made of tungsten-rhenium alloy, and the stirring head dimensions are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm. The stirring head speed is 800rpm, and the forward speed is 50mm / min, and then the magnesium alloy sample after stir friction processing is obtained.
[0075] Example 5
[0076] Example 5 provides a method for regulating the degradation rate of biological magnesium alloy in the urinary system, which specifically comprises the following steps:
[0077] S1, smelting of magnesium alloy: supply smelting raw materials to the resistance furnace for smelting, wherein the above smelting raw materials are configured according to the following mass percentage ratio: Y: 3wt.%, Nd: 1wt.%, Gd: 1wt.%, Zn: 1wt.%, Ca: 0.5wt.%, and the balance is Mg and other impurity elements. Put the raw materials into a ceramic crucible, and under the protection of a mixed gas atmosphere of 99% CO2-1% SF6, raise the temperature of the resistance furnace to 700°C, keep it warm for 30 minutes, and take out the magnesium alloy ingot after the furnace cools down.
[0078] S2, homogenization treatment: subjecting the magnesium alloy to a component homogenization heat treatment under the protection of an argon atmosphere, wherein the heat treatment temperature is 400° C. and the time is 12 h. The treated ingot is cooled to room temperature with the furnace to obtain a matrix material.
[0079] S3, processing process: first, the homogenized matrix material is cut into plates with a size of 200mm×65mm×4mm by wire cutting, and then the magnesium-rare earth alloy plate is surface polished to remove the oxide scale on the surface of the magnesium alloy, and then the magnesium alloy plate is subjected to stir friction processing. The stirring head is made of tungsten-rhenium alloy, and the stirring head dimensions are: shoulder diameter 15mm, stirring needle diameter 6mm, and stirring needle length 2.4mm. The stirring head speed is 1200rpm, and the forward speed is 50mm / min, and then the magnesium alloy sample after stir friction processing is obtained.
[0080] Figure 1 The magnesium alloy matrix material prepared in Example 1 ( Figure 1 a, represented by cast magnesium alloy) and the material after friction stir processing ( Figure 1 Surface SEM microstructure of b) Figure 1 In a, it can be observed that a large number of coarse precipitates are distributed on the surface of the magnesium alloy matrix material, and after friction stir processing ( Figure 1b) The precipitated phase is small and evenly distributed.
[0081] Figure 2 The polarization curve test results of the magnesium alloy matrix material prepared in Example 2 and the biological magnesium alloy sample after stir friction processing in artificial urine are shown in Figure 2. By Tafel fitting the polarization curve, the corrosion current density of the cast magnesium-rare earth alloy is 2.5×10 -4 A / cm 2 , while the corrosion current density of magnesium-rare earth alloy material after friction stir processing was greatly reduced to 1.2×10 -4 A / cm 2 .
[0082] Figure 3 The results of hydrogen evolution test of the magnesium alloy matrix material prepared in Example 4 and the biological magnesium alloy sample after stir friction processing in artificial urine show that the average daily hydrogen evolution amount of the casting alloy reaches 35 ml / cm 2 / day, the hydrogen evolution rate of the bio-magnesium alloy sample prepared in this embodiment is about 3ml / cm 2 / day.
[0083] Figure 4 The magnesium alloy matrix material prepared in Example 5 ( Figure 4 a, represented by cast magnesium alloy) and the bio-magnesium alloy sample after friction stir processing ( Figure 4 (b) Surface SEM morphology after long-term immersion test in artificial urine (degradation for 5 days and 15 days). The results show that after the design and processing of the magnesium alloy material, a uniform degradation process can be achieved in the artificial urine environment.
[0084] Figure 5 For different embodiment materials and base materials (in Figure 5 The degradation rate of the magnesium alloy (abbreviated as substrate) in the artificial urine environment is different. According to the preparation and processing methods proposed in this technology, the preparation of biological magnesium alloys with different degradation rates in the urinary system can be achieved, and the degradation rate control range is about (0.5~6mm / y).
[0085] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementation methods", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0086] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for regulating the degradation rate of biological magnesium alloy in the urinary system, characterized in that: include: S1: smelting the magnesium alloy raw material under a protective atmosphere to obtain a magnesium alloy ingot; The magnesium alloy raw material is composed of the following components in weight percentage: Y: 2-3wt.%, Nd: 1-2wt.%, Gd: 0-1wt.%, Zn: 0-1wt.%, Ca: 0-1wt.%, Sr: 0-1wt.%, and the balance of magnesium and impurity elements; S2: performing homogenization heat treatment on the magnesium alloy ingot under an inert atmosphere, and cooling the ingot to obtain a matrix material; S3: performing friction stir processing on the base material to obtain a bio-magnesium alloy of a predetermined size.
2. The method according to claim 1, characterized in that The protective atmosphere in step S1 is a mixed gas of CO2 and SF6; Optionally, the volume fraction ratio of the CO2 and the SF6 is 99:1-5.
3. The method according to claim 1, characterized in that The magnesium alloy raw material includes raw materials of the following components: Master alloy Mg-30wt.%Y, master alloy Mg-30wt.%Nd, master alloy Mg-30wt.%Gd, master alloy Mg-20wt.%Sr, pure Mg, pure Zn and pure Ca raw materials.
4. The method according to claim 1, characterized in that The temperature of the smelting treatment is 650-750° C., and the time of the smelting treatment is 10-30 minutes.
5. The method according to claim 1, characterized in that In step S2, a homogenization heat treatment is performed under the protection of an argon atmosphere; Optionally, the heat treatment temperature is 300°C-450°C, and the time is 12-24h.
6. The method according to claim 1, characterized in that In step S3, the stirring head used in the friction stir processing is a tungsten-rhenium alloy; Optionally, in step S3, the forward speed of the stirring head used in the friction stir processing is 10-200 mm / min; Optionally, in step S3, the stirring head used in the friction stir processing has a rotation speed of 100-1500 rpm.
7. The method according to claim 1, characterized in that In an artificial urine environment, the corrosion current density of the biological magnesium alloy is 10-500 μA / cm 2 The degradation rate is 0.5~40mm / y.
8. A method for preparing a biological magnesium alloy for the urinary system, characterized in that: include: S1: melting the magnesium alloy raw material under a protective atmosphere to obtain a magnesium alloy ingot; Wherein, the magnesium alloy raw material includes Y: 2-3wt.%, Nd: 1-2wt.%, Gd: 0-1wt.%, Zn: 0-1wt.%, Ca: 0-1wt.%, Sr: 0-1wt.%, and the balance of magnesium and impurity elements; S2: performing homogenization heat treatment on the magnesium alloy ingot under an inert atmosphere, and cooling the ingot to obtain a matrix material; S3: performing friction stir processing on the base material to obtain a bio-magnesium alloy of a predetermined size.
9. A bio-magnesium alloy, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the bio-magnesium alloy according to claim 9 in preparing biomaterials for the urinary system.
Citation Information
Patent Citations
Mg-Zn-Sr-Ca system magnesium alloy and preparation method thereof
CN103725942A
Degradable biomedical Mg-Nd-Sr magnesium alloy as well as preparation method and application thereof
CN105154735A
Medical Mg-Gd-Zn (-Ca) magnesium alloy with LPSO structure and preparation method thereof
CN106244882A
Anti-aging high-toughness corrosion-resistant double-phase magnesium-lithium alloy and preparation method thereof
CN113528911A
Degradable ultra-fine grain biological magnesium alloy and preparation method thereof
CN114075629A